Style of lecturing of medical teacher - an evaluation by medical students of Mymensingh Medical College - Shahidullah, SM; Haque, MM; Nasreen, SA; Sultana, S (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jul;15(2):120-3 The abstract of this article is available on the PubMed website